The Influence of Teacher’s Teaching Methods on Students’ Learning Enthusiasm - Budiarti Putri Uleng; Muthmainnah Abu; Mahfuddin, Musyrifah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research aimed at finding out whether the teacher’s teaching methods influence learning enthusiasm of the students of SMAN 8 Makassar. This research employed a QUAN-Qual model. The population of this research involved 350 students from the eleventh grade. The participants of this research were 27 students of class XI IPS 2 and an English teacher. This class was taken as the sample through random sampling technique from 10 classes. The data were collected through the observation checklist, questionnaire, and interview. The findings of this research revealed that the English teacher’s teaching method of SMAN 8 Makassar Selatan influenced the students’ learning enthusiasm. It was proven by the result of the observation checklist, questionnaire, and interview. The observation checklist presented the teacher’s teaching method during the classroom which missed some indicators. The observation checklist for the students indicated less enthusiasm strengthened by the questionnaire revealing that most students were in moderate state of enthusiasm or in other words they have low degree of learning enthusiasm. Meanwhile, the result of the interview strengthened the data from observation checklist and questionnaire that the English teacher’s teaching method contributed to the students’ learning enthusiasm. Thus, the teacher’s teaching method is a determining factor of the students’ enthusiasm in learning especially learning English.